Therapy With Intravenous Methylprednisolone Pulses Is Associated With Loss of Bone Microarchitecture in Trabecular Bone Score -Assessment Among Patients With Moderate-to-Severe Graves’ Orbitopathy: A Pilot Study - Rymuza, Joanna; Pelewicz, Katarzyna; Przedlacki, Jerzy; Miśkiewicz, Piotr (Frontiers in Endocrinology, 2022)
Background Therapy with intravenous glucocorticoids (GCs) is associated with various side effects, however, the impact on bone remains elusive. Trabecular bone score (TBS) is a diagnostic tool providing information on bone microarchitecture based on images obtained from dual-energy X-ray absorptiometry. We investigated the influence of the intravenous methylprednisolone (IVMP) pulse administration on TBS in patients with moderate-to-severe Graves’ orbitopathy (GO). Methods Fifteen patients with GO were treated 12 IVMP pulses (6x0.5g, 6x0.25 g on a weekly schedule). They received supplementation with 2000 IU of vitamin D and 1.0 g of calcium throughout the study period. TBS was assessed at baseline and after last IVMP pulse. To determine the difference between values at baseline and after treatment the least significant change (LSC) methodology was used. We compared pre- and posttreatment mean TBS values too. Results We found a significant decrease of TBS in 5 out of 15 (33%) patients. Mean TBS value decreased becoming 2.4% lower than at baseline (p<0.05). Conclusions IVMP pulse therapy exerts negative effect on bone microarchitecture in TBS assessment. The analysis of the clinical risk factors for osteoporosis and the evaluation of bone mineral density and TBS should be considered before initiating IVMP therapy.